Estimation of Patient Accrual Rates in Clinical Trials Based on Routine Data from Hospital Information Systems - Dugas, M.; Amler, S.; Lange, M.; Gerß, J.; Breil, B.; Köpcke, W. (Methods of Information in Medicine, 2009)
Background: Delayed patient recruitment is a common problem in clinical trials. According to the literature, only about a third of medical research studies recruit their planned number of patients within the time originally specified.Objectives: To provide a method to estimate patient accrual rates in clinical trials based on routine data from hospital information systems (HIS).Methods: Based on inclusion and exclusion criteria for each trial, a specific HIS report is generated to list potential trial subjects. Because not all information relevant for assessment of patient eligibility is available as coded HIS items, a sample of this patient list is reviewed manually by study physicians. Proportions of matching and non-matching patients are analyzed with a Chi-squared test. An estimation formula for patient accrual rate is derived from this data.Results: The method is demonstrated with two datasets from cardiology and oncology. HIS reports should account for previous disease episodes and eliminate duplicate persons.Conclusion: HIS data in combination with manual chart review can be applied to estimate patient recruitment for clinical trials.
Keywords: Patient accrual rate; hospital information system; clinical trial